ANALISIS PENGGUNAAN GASOHOL DARI LIMBAH KULIT PISANG TERHADAP PRESTASI MESIN MOTOR BAKAR BENSIN - Piarah, Wahyu H.; Djafar, Zuryati; Mangkau, Andi (Jurnal MEKANIKAL, 2011)
Usage of type alcohol of etanol in gasoline fuel proves a number of machine achievements in terms of parameters, namely actual horsepower, specific fuel consumption, mean effective pressure and thermal efficiency compared to use pure premium fuel. Level of such repair gyrate 73% from maximum energy according to machine specification. In yielding etanol, fermentation process with yeast mixture then destiltaion. Etanol mixed with premium with certain ratio. In this research, variation of mixing of alcohol premium, namely: 95%+5%; 90%+10% and 85%+15% by 3 variation Â throttle opening: 20%, 40% and 60%. The result indicates that with usage of concentration mixing of premium + etanol, reached actual horsepower by Kijang machine 7k experiencing with maximum value equal to 17,347 kW that happened at condition of opening of throttle 60% at rotation 2100 rpm with usage of mixing 95% premium + 5% etanol. With usage of concentration mixing of premium + etanol, specific fuel consumption also experience with maximum value equal to 0,331 kg/ kWh that happened at condition of throttle opening by 20% within rotation of 2100 rpm with usage of mixing 90% premium + 10% etanol.